Estimation of spectral velocity at long periods for application in velocity dependant seismic energy management devices - Desai, R.S.; Tande, S.N. (Journal of Structural Engineering, 2024)
In response spectrum method of structural analysis spectral displacement (SD ), spectral velocity obtained by undamped natural frequency times SD called pseudo spectral velocity (PSV), and pseudo spectral acceleration (PSA) are the response quantities used in general. FEMA356 classifies energy dissipation devices in different categories and specifies four distinct methods of analysis and design of structures installed with these devices. Pseudo spectral velocity is recommended by it to estimate damping forces in the velocity responding devices and subsequent structural response. As reported in literature, for accurate seismic response analysis of longer period structures using such devices, peak relative velocity (SV) value is more appropriate to be used in place of PSV, which is able to capture true forces in the devices. In view of this, new methodology of approximating SV values from PSV is proposed in this study which is useful for structures using velocity responding energy dissipation devices. Ensemble of several earthquake records with wide variations in their characteristics from all over the world are used to derive the proposed estimation of SV from PSV and to verify its accuracy. It is shown that proposed approximation rule performs better than other available approximations at longer periods. It is suggested to use combined approximation which yields reasonably accurate SV values for short, intermediate and long periods.